2019
DOI: 10.4143/crt.2018.221
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Changes in Prostate Cancer Patients after Radical Prostatectomy: A Longitudinal Cohort Study

Abstract: Most HRQOL domains showed recovery within 12 months after RP, excluding sexual functioning and social functioning. Our findings may guide patients considering surgical treatment for PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
9
1
1
Order By: Relevance
“…In our study, we noted a slight but significant reduction (improvement) of the psychological subscore (irritability, nervousness, and anxiety) of the AMS (0.58, 95% CI: 0.25–0.91; P = 0.0003) 1 year after radical prostatectomy. This result is in line with the improved emotional and cognitive functioning 12 months after radical prostatectomy reported in a prospective longitudinal cohort ( n = 209) of prostate cancer patients treated with radical prostatectomy, 23 possibly consequent to patients' relief as the expected that the malignant tumor had been removed. One should be aware that this improvement was not sufficient to compensate for the sexual dysfunction as shown by the worsening of the global AMS score.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, we noted a slight but significant reduction (improvement) of the psychological subscore (irritability, nervousness, and anxiety) of the AMS (0.58, 95% CI: 0.25–0.91; P = 0.0003) 1 year after radical prostatectomy. This result is in line with the improved emotional and cognitive functioning 12 months after radical prostatectomy reported in a prospective longitudinal cohort ( n = 209) of prostate cancer patients treated with radical prostatectomy, 23 possibly consequent to patients' relief as the expected that the malignant tumor had been removed. One should be aware that this improvement was not sufficient to compensate for the sexual dysfunction as shown by the worsening of the global AMS score.…”
Section: Discussionsupporting
confidence: 84%
“… 53 Similarly, a previous cohort study showed a significant improvement in most health-related quality of life domains 12 months after treatment of prostate cancer. 54 In contrast, another study by Klein et al reported a lower health-related quality of life on an overall global scale and all functional domains of quality of life. 55 In addition, a Korean study revealed a lack of improvement in urinary and sexual outcomes in prostate cancer patients after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 90%
“…The long-term ADT group, maintained on androgen suppression for 2.5 years, showed further decrease in the functional levels, whereas the short-term group, which discontinued ADT after 6 months, showed no further decrease. 18 Meanwhile, Shin et al 19 conducted a study on the change in the HRQOL according to surgical treatment in patients with PC and reported that surgery had no negative effect on the QLQ-C30 functional scale score over a time period of 1 year, except for the deterioration of the role function. Role function had a temporary decline at 3 months after surgery but returned to baseline at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al. 19 reported that the PC-specific HRQOL of Korean patients, as assessed using the EORTC QLQ-PR25, showed a significant deterioration of most symptom scores, with the exception of bowel symptoms, at 3 months postoperatively compared with the baseline condition after radical prostatectomy. The urinary symptoms worsened at 3 months, and incontinence significantly worsened at 3 months, although patients recovered to nearly the baseline status at 12 months.…”
Section: Discussionmentioning
confidence: 99%